Dialectic of Public Sphere vs. Private Sphere in Millennial Families in Lampung Customary Law Community - Zulaikha, Siti; Nasrudin, Muhamad; Lestari, Enny Puji (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
Lampung’s patriarchal customary law faces severe challenges from the millennial generation, who constitute more than 29% of the total population of Lampung. This challenge is based on the fundamental character of the millennial generation, who are open-minded and obtain the opportunity of having an interethnic marriage. This article maps the dialectic of the public sphere vs. private sphere in millennial families in the Lampung customary law community and how women’s strategies survive the confines of patriarchy. This article explored data from a millennial married couple who live in four districts/cities in Lampung using a qualitative, socio-legal study approach standing with ten principles of marriage on happy family (SMART)’s Khoiruddin Nasution. The findings: The boundaries between the public and the private were no longer tight because husband and wife could work collaboratively, even though there were some challenges due to the dominance of patriarchal mindset in extended families, which was sometimes affirmed, even enjoyed by the husband. However, the subconscious of the millennial family was still patriarchal even though it no longer applied strictly at the practical level. Meanwhile, women survived passively by taking advantage of the economic conditions of their families or changing environments. In addition, the active strategy is to improve formal education; live separately from the extended family; have a stable job (before marriage), and manage working time